Solution of Riccati equation - Petrauskas, Kostas Ramutis; Skučas, Ignas; Petrauskienė, Irena; Būda, Antanas (Lietuvos matematikos rinkinys, 2002)
An analytical expression of general solution of Riccati equation is received. An analytical expression of general solution of second-order differential linear equation is received by solving Riccati equation.